Penyusunan Kurikulum Perguruan Tinggi Keagamaan Kristen Mengacu pada Kerangka Kualifikasi Nasional Indonesia - Oci, Markus; Stevanus, Kalis (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2021)
The rapid development of Science and Technology in the era of the Industrial Revolution 4.0 has influenced various aspects of human life, both in the world of work and the world of education. The purpose of this article is written with the hope that Christian Religious Colleges can answer the challenges of the Industrial Revolution 4.0 in order to produce human resources or graduates who are able to compete in the midst of global competition. One of the steps is to reconstruct a curriculum that is responsive to technological developments. The compilation and implementation of curricula at Christian Religious Colleges must refer to KKNI and the National Higher Education Standards. The research method used is qualitative research with a literature study approach. The analysis process carried out is to use various literary sources, both journals, books and other reliable reference materials to support the author's analysis. Thus it can be concluded that there are six steps in the preparation of the curriculum for Christian Religious Higher Education which refers to the Indonesian National Qualifications Framework (KKNI): 1. Formulating a Graduate Profile; 2. Formulating Graduate Learning Outcomes; 3. Determine the Study Material; 4. Compiling Subjects; 5. Determining the Structure of the Course and, 6. Developing a semester learning plan (RPS). Derasnya perkembangan Ilmu Pengetahuan dan Teknologi di era Revolusi Industri 4.0 telah mempengaruhi pelbagai aspek kehidupan manusia, baik di dunia kerja maupun dunia pendidikan. Tujuan artikel ini ditulis dengan harapan Perguruan Tinggi Keagamaan Kristen dapat menjawab tantangan Revolusi Industri 4.0 guna menghasilkan sumber daya manusia atau lulusan yang mampu bersaing di tengah persaingan global. Salah satu langkahnya adalah merekonstruksi kurikulum yang responsif terhadap perkembangan teknologi. Penyusunan dan pelaksanaan kurikulum di Perguruan Tinggi Keagamaan Kristen wajib mengacu pada KKNI dan Standar Nasional Pendidikan Tinggi. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan studi pustaka. Proses analisis yang dilakukan adalah menggunakan berbagai sumber literatur-literatur baik jurnal, buku dan bahan referensi lainnya yang terpercaya untuk mendukung analisis penulis. Dengan demikian dapat disimpulkan ada enam langkah dalam penyusunan kurikulum Perguruan Tinggi Keagamaan Kristen yang mengacu pada Kerangka Kualifikasi Nasional Indonesia (KKNI): 1. Merumuskan Profil Lulusan; 2. Merumuskan Capaian Pembelajaran Lulusan; 3. Menentukan Bahan Kajian; 4. Menyusun Matakuliah; 5. Menetapkan Struktur Matakuliah dan, 6. Menyusun Rencana pembelajaran semester (RPS).